Safety of hyperbaric oxygen therapy for management of central airway stenosis after lung transplant. Issue 9 (2nd August 2016) - Mahmood, Kamran; Kraft, Bryan D.; Glisinski, Kristen; Hartwig, Matthew G.; Harlan, Nicole P.; Piantadosi, Claude A.; Shofer, Scott L.
Abstract: Background: Central airway stenosis (CAS) is common after lung transplantation and causes significant post‐transplant morbidity. It is often preceded by extensive airway necrosis, related to airway ischemia. Hyperbaric oxygen therapy (HBOT) is useful for ischemic grafts and may reduce the development of CAS. Methods: The purpose of this study was to determine whether HBOT could be safely administered to lung transplant patients with extensive necrotic airway plaques. Secondarily, we assessed any effects of HBOT on the incidence and severity of CAS. Patients with extensive necrotic airway plaques within 1–2 months after lung transplantation were treated with HBOT along with standard care. These patients were compared with a contemporaneous reference group with similar plaques who did not receive HBOT. Results: Ten patients received HBOT for 18.5 (interquartile range, IQR 11–20) sessions, starting at 40.5 (IQR 34–54) days after transplantation. HBOT was well tolerated. Incidence of CAS was similar between HBOT‐treated patients and reference patients (70% vs 87%, respectively; P =.34), but fewer stents were required in HBOT patients (10% vs 56%, respectively; P =.03). Conclusions: This pilot study is the first to demonstrate HBOT safety in patients who develop necrotic airway plaques after lung transplantation. HBOT may reduce the need for airway stent placement in patients with CAS.